Indonesian Food Production Challenges: Climate, Land and Industrialization - Setiawan, Avi Budi; Nugroho, Agus Dwi; Wiyanti, Dian Tri; Yusuf, Mochammad; Maslikhatun, Anjani; Bowo, Prasetyo Ari (JEJAK: Jurnal Ekonomi dan Kebijakan, 2023)
The increase in agricultural production has become a global issue related to food security. Indonesia faces challenges in fulfilling its food needs. Climate change, land conversion, and industrialization play a role in food crop production. This study aims to examine the short-term and long-term effects of climate change, land conversion, and industrialization on the food production index. The analysis method used is the Autoregressive Distributed Lag (ARDL). The ARDL analysis was chosen because it can explain the short-term and long-term effects as well as the effects at each lag time. The results showed that there is positive and significant long-term cointegration or influence between rainfall, per capita energy consumption, agricultural land area, and forest area on the food production index. There is also a significant negative long-term effect between air temperature, industrialization, and population density on the food production index. In the short term, the previous year's food production, land area and forest area, air temperature, energy consumption, rainfall in two and three years ago, current of industrial share, and one and two years ago industrial share, population density two years ago influence the current food production index. The conclusion and findings of this study are that there is long-term cointegration and short-term effects at different lag times for climate change, land conversion, and industrialization variables on the food production index.